The performance of NXP Semiconductors Sdn Bhd: analysis based on profitability and creditability / Nur Asmiza Amirnuddin - Amirnuddin, Nur Asmiza (2010)
This study is concern to the NXP Semiconductors Sdn Bhd performance as the significant indicator of having a good financial performance. In order to obtain a good financial performance, an appropriate analysis or evaluation need to be conducted. Rationally, the purpose of preparing and analysis or evaluation is to show is establishing of a company depend to its financial performance and have an ability to manage the utilization of its sources. With the stability of its financial performance, there is no impossible to a company to have continuous operation. Assist from financial statement and a balance sheet, an analysis or the evaluation can be conducted. To have an analysis to this study, the financial tools will be used to measure. The analytical tools such as financial ratio will be measured as represented in the financial statement dated 2006 to 2009. Each of financial ratios bringing the different kind of description to is as the evaluation or the analysis after being done. There are several different of financial ratios and profitability and credibility will be stress on in the study. In profitability ratios consists of the net profit margin, gross profit margin, operating profit margin, return on assets (ROA) and return on equity (ROE). Otherwise, for credibility include current ratio, total debt to equity and time interest earned. Based on the research, researcher found that NXP’s facing the net losses towards the profits and it was high credit (risk) regarding the long-term debt. Indeed, the good management from it assets affected the financial performance. For recommendation, reduce expenses and arise the profits in their sales/revenue and COGS. Thus, the actual margin of the analysis describes the details of the profitability and creditability ratios.